Methods of research in social sciences (survey, observation and interview) (Journal of Philosophy Culture and Political Science, 2018)
The article is deeply considered the methods of research in field of social sciences and also applied in practice. The article describes the methods of surveying, observation and interviewing, and describes their experience, which was used in practice. We used the survey method to investigate such a political act as «on amending the Constitution in connection with the redistribution of the president’s authority between the branches of power.» In this article was described from the method of constructing the sample to the results of the study. In conclusion they described the relationship of society to political processes. The second method which we used for research is a method of observation. Our goal was to use this method to describe «General characteristics and mechanisms of the fraud of network marketing in the city of Almaty». To complete this research, we used the interview method. We interviewed people who were victims of network marketing. Using the interview method, we talked with several people and made common similar moments of network marketing.Using these scientific methods, we tried to investigate the actual problems of society. As a result ofthe research, we identified «The attitude of society towards the redistribution of the president’s authorityand the 26th article which was relevant on that moment», made «Common similarities of networkmarketing».Key words: methods, survey, observation, interview, science.